Pengaruh Model Pembelajaran Berbasis Kemampuan terhadap Hasil Belajar Mahasiswa Perguruan Tinggi - Muhammad Fajar Firdausyi; Dede Kurniawan; Wawan Hermawan; Ria Rahmawati (Departement of Mathematics Education, 2020)
This research examines the extent of the influence of ability-based learning models on student learning outcomes in higher education. This research was carried out using a literacy approach or often called literature study using secondary data in the form of books and also reference sources from previous researchers which have been published in journals, both national and international. The ability-based learning model has a positive impact on student learning outcomes in higher education. With a focus on developing practical skills, conceptual understanding, and critical thinking abilities, this approach helps students become better prepared to face real-world demands after graduation. Therefore, universities need to consider using ability-based learning models in an effort to improve the quality of brand education. Several opportunities for further research related to ability-based learning can be carried out on the grounds of Educational Evolution, Attention to 21st Century Skills, Emphasis on Deep Learning Outcomes, Variations in Application, Increasing Student Motivation, Evaluation of the Impact of Technology and the Need to Improve the Quality of Education.